Optimizing different damaged reinforced concrete corbel characteristics utilizing CFRP sheets - Salah Aborgheef; Abdulkhalik Jabbar Abdulridha (Fracture and Structural Integrity)
Concrete corbels are short cantilever constructions that may lose their strength over time because of loads that happen over and over again. As an external bonding method for reinforcement, carbon fiber-reinforced polymer (CFRP) strips are utilized to improve performance. This study examines the influence of CFRP strips on the reinforcement and repair of conventional concrete corbels by concentrating on ultimate strength, performance under monotonic loads, and the effects of varying damage ratios during restoration. As part of a study project, nine double-concrete corbels with the same size and reinforcement had to be manufactured and tested. The samples were split into two groups: those with strip wrapping and those with side wrapping. Each group had three corbels that had already been damaged, one corbel that had been reinforced, and control specimens that had not been repaired. The results showed that side-wrapped corbels with CFRP reinforcement exhibited a 19.72% (SCS-0-1) improvement in strength and a 13.73% (RCS-50-1), 18.35% (RCS-60-1), and 4.15% (RCS-70-1) increase in ultimate load. Strip-wrapped corbels showed improvements of 9.86% (RCST-50-2), 5.44% (RCST-60-2), and 0.51% (RCST-70-2), whereas strengthening (SCST-0-2) showed an improvement of 19.72%. Also, specimens wrapped in CFRP showed less ultimate deflection than their un-strengthened counterparts at the same damage levels, which shows that they perform better and last longer.